Patient Safety Culture in Hospitals based on Agency For Health Care Research And Quality (AHRQ) - Wahyuningsih, Christiana Sri; Asih, Esthi Budhi; Masitoh, Rohayati; Rahmawati, Kiki (Journal of Health Policy and Management, 2024)
Background: The first step towards patient safety is to build a good patient safety culture. Patient safety culture measurements can be used as evaluations to improve quality and patient safety. This study aims to determine an overview of patient safety culture in hospitals. Study Method: It was a descriptive observational study with a cross-sectional study conducted in July 2022 - September 2022. This study was conducted at Panembahan Senopati Hospital with a total population of 974 hospital employees and selected 383 study samples by using simple random sampling. The dependent variable in the study was patient safety culture. The independent variables in this study were information disclosure, feedback and communication about patient safety incidents, management support for patient safety, non-punitive response to errors, organizational learning and continuous improvement, staffing, staff expectations of supervisor/management attitudes and actions in encouraging patient safety, cooperation within the unit, frequency of incident reporting, overall perception on safety, handoff and transition, and cross units cooperation. The data collection technique used was the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire developed by the Agency for Health Care Research Quality (AHRQ) consisting of 12 dimensions of patient safety culture. The study data were analyzed using descriptive analysis technique. Result: The positive value of patient safety culture fell into the medium category (72.12%). The dimensions of patient safety culture with strong categories (>75%) were cooperation within the unit, expectations and actions of managers in promoting patient safety, organizational learning, management support for patient safety, and cross units cooperation. The dimensions of patient safety culture in the medium category (50% - 75%) were employee perceptions of patient safety, feedback and communication on errors, open communication, frequency of incident reporting, handoffs and transitions, and non-punitive responses to errors. The dimension of patient safety culture with weak category (< 50%) was staffing. Conclusion: The strength areas of patient safety culture are organizational aspects, aspects of management support for patient safety, aspects of cross units cooperation, aspects of cooperation within units, and expectations and actions of managers in promoting patient safety. While the areas that still require development are staffing aspects, open communication aspects, and incident reporting frequency, thus their improvement must be prioritized. Keywords: AHRQ, patient safety, safety culture Correspondence: Christiana Sri Wahyuningsih. Panembahan Senopati General Hospital Bantul, Jl. Dr. Wahidin Sudiro Husodo, Trirenggo, Bantul, Bantul, Yogyakarta. Email: anachristi19@gmail.com. Mobile: +6281287783924